2020
DOI: 10.3390/atmos12010036
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Impact of Atmospheric Warming on Staple Crop Growth in China in the 1960s and 2000s

Abstract: Responses of crop growth to climate warming are fundamental to future food security. The response of crops to climate change may be subtly different at their growing stages. Close insights into the differentiated stage-dependent responses of crops are significantly important in making adaptive adjustments of crops’ phenological optimization and cultivar improvement in diverse cropping systems. Using the Agro-C model, we studied the influence of past climate warming on crops in typical cropping systems in China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…It indicated that MC hydrogels absorbed water more easily at a temperature lower than LCST (25 • C). However, the higher temperature (~30 • C) favored crop growth [111]. Thanks to the remarkable temperature-responsive features of MC hydrogel, its fertilizer release rate was elevated at a warmer temperature, which guaranteed the ample supply of nutrients for sustained crop growth.…”
Section: Multi-responsive Cellulose Fertilizer Hydrogelsmentioning
confidence: 99%
“…It indicated that MC hydrogels absorbed water more easily at a temperature lower than LCST (25 • C). However, the higher temperature (~30 • C) favored crop growth [111]. Thanks to the remarkable temperature-responsive features of MC hydrogel, its fertilizer release rate was elevated at a warmer temperature, which guaranteed the ample supply of nutrients for sustained crop growth.…”
Section: Multi-responsive Cellulose Fertilizer Hydrogelsmentioning
confidence: 99%